Iron Oxidation by a Fused Cytochrome-Porin Common to Diverse Iron-Oxidizing Bacteria - Jessica L. Keffer (American Society for Microbiology, 2021)
ABSTRACT Iron (Fe) oxidation is one of Earth’s major biogeochemical processes, key to weathering, soil formation, water quality, and corrosion. However, our understanding of microbial contribution is limited by incomplete knowledge of microbial iron oxidation mechanisms, particularly in neutrophilic iron oxidizers. The genomes of many diverse iron oxidizers encode a homolog to an outer membrane cytochrome (Cyc2) shown to oxidize iron in two acidophiles. Phylogenetic analyses show Cyc2 sequences from neutrophiles cluster together, suggesting a common function, though this function has not been verified in these organisms. Therefore, we investigated the iron oxidase function of heterologously expressed Cyc2 from a neutrophilic iron oxidizer Mariprofundus ferrooxydans PV-1. Cyc2PV-1 is capable of oxidizing iron, and its redox potential is 208 ± 20 mV, consistent with the ability to accept electrons from Fe2+ at neutral pH. These results support the hypothesis that Cyc2 functions as an iron oxidase in neutrophilic iron-oxidizing organisms. The results of sequence analysis and modeling reveal that the entire Cyc2 family shares a unique fused cytochrome-porin structure, with a defining consensus motif in the cytochrome region. On the basis of results from structural analyses, we predict that the monoheme cytochrome Cyc2 specifically oxidizes dissolved Fe2+, in contrast to multiheme iron oxidases, which may oxidize solid Fe(II). With our results, there is now functional validation for diverse representatives of Cyc2 sequences. We present a comprehensive Cyc2 phylogenetic tree and offer a roadmap for identifying cyc2/Cyc2 homologs and interpreting their function. The occurrence of cyc2 in many genomes beyond known iron oxidizers presents the possibility that microbial iron oxidation may be a widespread metabolism. IMPORTANCE Iron is practically ubiquitous across Earth’s environments, central to both life and geochemical processes, which depend heavily on the redox state of iron. Although iron oxidation, or “rusting,” can occur abiotically at near-neutral pH, we find neutrophilic iron-oxidizing bacteria (FeOB) are widespread, including in aquifers, sediments, hydrothermal vents, pipes, and water treatment systems. FeOB produce highly reactive Fe(III) oxyhydroxides that bind a variety of nutrients and toxins; thus, these microbes are likely a controlling force in iron and other biogeochemical cycles. There has been mounting evidence that Cyc2 functions as an iron oxidase in neutrophiles, but definitive proof of its function has long eluded us. This work provides conclusive biochemical evidence of iron oxidation by Cyc2 from neutrophiles. Cyc2 is common to a wide variety of iron oxidizers, including acidophilic and phototrophic iron oxidizers, suggesting that this fused cytochrome-porin structure is especially well adapted for iron oxidation.